Culture in sustainable development: investing in cultural and natural endowments - Serageldin, Ismail; Martin-Brown, Joan
This is the proceedings of the Conference on Culture in Sustainable Development: Investing in Cultural and Natural Endowments held at Washington DC on September 28-29, 1998, sponsored by the Bank and the United Nations Educational, Scientific, and Cultural ... See More + Organization (UNESCO). It addresses the social and economic opportunities and requirements to mainstream investments in cultural heritage and the living arts. The two-day deliberations included attention to questions of equity, social inclusion, the opportunities to redress conditions of poverty, and the collective capacities to preserve and conserve cultural and natural heritage through partnerships.